Synthesis and characterization of poly(proyleneimine)-based Rhodium(I) Metallodendrimers and their evaluation as Hydroformylation catalysts - Antonels, Nathan (Department of Chemistry, 2014)
A series of new iminopyridyl- and iminophosphine-functionalized dendritic ligands were synthesized by reacting the commercially available first and second-generation DAB poly(propyleneimine) (PPI) dendrimers with 4-pyridinecarboxaldehyde and 2-(diphenylphosphino)benzaldehyde respectively via a Schiff-base condensation reaction. The ligands were characterized using NMR and IR spectroscopies, elemental analyses and mass spectrometry. Model monomeric analogues of these multimeric ligands were synthesized to aid with interpreting the more complex spectra of the dendritic ligands. The iminopyridyl-functionalized ligands were reacted with [RhCl(COD)]2 to yield a set of new mononuclear and multinuclear rhodium(I) complexes that coordinated selectively to the pyridyl nitrogen in a monodentate coordination mode. The iminophosphine functionalized ligands were reacted with [RhCl(CO)2]2. These reactions yielded a set of new mononuclear and multinuclear iminophosphine rhodium(I) complexes, where the P,N-donor iminophosphine ligands coordinated to the rhodium metal center in a heterobidentate coordination mode to form chelate complexes. The complexes were characterized using NMR and IR spectroscopies, elemental analyses and mass spectrometry. Crystals of the mononuclear iminophosphine rhodium(I) complex were obtained and the molecular structure solved using single crystal X-ray diffraction analysis. Chemical reactivity studies were conducted on the mononuclear and multinuclear iminopyridyl and iminophosphine complexes. The iminopyridyl rhodium(I) complexes were reacted with triphenylphosphine. These reactions yielded similar results to that of the reaction between the iminopyridylfunctionalized ligands and [RhCl(PPh3)3]. Methyl iodide was reacted with the mononuclear and multinuclear iminophosphine rhodium(I) complexes. Reactions of methyl iodide with the mononuclear iminophosphine rhodium(I) complex yielded a mixture of the oxidative addition and the acyl product, where the acyl product results from a subsequent alkyl migration into the metal carbonyl bond after oxidative addition has occurred. Reaction of methyl iodide with the multinuclear metallodendritic iminophosphine rhodium(I) complexes yielded the oxidative addition product exclusively. Reaction products were monitored using IR spectroscopy. Selected mononuclear and multinuclear iminopyridyl and iminophosphine rhodium(I) complexes were evaluated as catalysts in the hydroformylation of 1-octene. The complexes showed moderate hydroformylation rates under mild conditions. The multinuclear metallodendritic rhodium(I) complexes compare favorably to that of the mononuclear rhodium(I) complexes showing slightly enhanced catalytic activity and regioselectivity in certain cases. Hydroformylation results obtained when using these complexes compare well to results obtained when using [Rh(acac)(CO)2] under similar conditions, a rhodium(I) complex commonly used in literature.